Analysis The Application of Game-Based Learning to Increas Student Interest at Class VIII-6 in Arabic Language Learning at MTs Darul Ulum Budi Agung - Ismi Khairani; Ainurrahmah Ainurrahmah; Desi Susanti; Sahkholid Nasution (Universitas Al-Amien Prenduan, 2025)
Arabic language learning often faces the challenge of low student interest, especially because it is considered difficult to understand letters, vocabulary, and grammar. Monotonous traditional learning approaches tend to make students feel bored and less involved in the learning process. To overcome this, the game-based learning method is applied as an innovative strategy to create a more interactive and fun learning atmosphere. This study aims to analyze the application of game-based learning in increasing students' interest in learning class VIII-6 at MTs Darul Ulum Budi Agung. By using descriptive qualitative method, the research data was collected through interviews, observations, and documentation during the learning process. The focus of the research included changes in students' attitudes, increased understanding of vocabulary (mufrodat), and the learning atmosphere created through educational games. The results showed that this method significantly increased students' interest in learning. Games such as flashcards and matching games help students understand vocabulary more easily and increase their engagement in learning. In addition, the classroom atmosphere became more dynamic and collaborative, encouraging previously passive students to participate more actively. In conclusion, game-based learning is an effective approach to increase interest in learning Arabic in junior high school. This method can be used as a relevant alternative learning model to face challenges in learning Arabic in various educational contexts.